2015
DOI: 10.1177/1060028015624204
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab Treatment for Allergic Bronchopulmonary Aspergillosis in Cystic Fibrosis

Abstract: This study showed steroid-sparing effect, decreasing IgE levels, and improvement in respiratory symptoms in 6 CF patients with omalizumab treatment. Although this is a small sample of the population, omalizumab may be an alternative therapy for ABPA in CF patients who fail to respond to systemic corticosteroids or have serious adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 16 publications
0
15
1
1
Order By: Relevance
“…In CF patients, previous studies have shown inconsistent results regarding predictors of response. Notably, in one case series [ 23 ], patients with severe initial disease did not improve FEV1pp on omalizumab whereas in another article omalizumab was less effective in patients with severe lung disease and long-term ABPA [ 24 ]. In our study, no significant correlations were observed between the levels of IgE before omalizumab initiation and the change in FEV 1 pp max value, the slope or the AUC while on omalizumab.…”
Section: Discussioncontrasting
confidence: 69%
“…In CF patients, previous studies have shown inconsistent results regarding predictors of response. Notably, in one case series [ 23 ], patients with severe initial disease did not improve FEV1pp on omalizumab whereas in another article omalizumab was less effective in patients with severe lung disease and long-term ABPA [ 24 ]. In our study, no significant correlations were observed between the levels of IgE before omalizumab initiation and the change in FEV 1 pp max value, the slope or the AUC while on omalizumab.…”
Section: Discussioncontrasting
confidence: 69%
“…There is recent evidence that treatment with omalizumab can decrease the risk of recurrent exacerbations. This argues for IgE's central role in the pathology of the disease process (10,11). Although a number of molds have been implicated as causes of ABPM, Aspergillus species are by far the most common -of which A. fumigatus is seen most commonly (12).…”
Section: Introductionmentioning
confidence: 99%
“…Omalizumab (300 mg dosage) was administered subcutaneously every 4 weeks to the patients who were treated previously with oral prednisolone and itraconazole. Decreased IgE levels, improvement in respiratory symptoms, and a steroidsparing effect was shown with omalizumab treatment (118). A retrospective multicenter observational French study retrieved 32 patients with ABPA and CF (11 children and 21 adults) who had received omalizumab for more than 3 months.…”
Section: Omalizumabmentioning
confidence: 99%